Morfometric Portrait of Swamp Buffalo in Bombana - Nafiu, La Ode; Saili, T.; Bain, A. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The aim of this study was to find a portrait of body weight and body size of swamp buffalo inmainland and islands of Bombana region. The parameters observed were: body weight, shoulderand hip height, body length, chest circumference and width of hips. Based on the results of the studyconcluded: (1) the average body weight of buffalo in the islands was 416.9±117 kg, significantlyhigher (P<0.05) compared with the mainland area which averaged only 377.3±100 kg, as well as theaverage hips width of swamp buffalo in island area was significantly higher (P<0.05) than in themainland, (2) portrait of body measurement of swamp buffalo generally not significantly different(P> 0.05) between the mainland and island regions, except the size of the hips width in the island wassignificantly higher (P<0.05) than the mainland, (3) the main component identifier of the totaldiversity of buffalo body measurements in mainland area was body length (69.30%), while the islandareas was chest circumference (73.50%).Key Words: Buffalo, Body Weight, Body Measurement, Principal Component Analysis